Influence of Adequate Educational Resources on the Administration of Senior Secondary Schools in Niger State - Yusuf, Shehu Bazata; Awwal, Ibrahim; Mohammed, Kabiru (International Journal of Educational Management, 2025)
This study was tagged Influence of Adequate Educational Resources on the Administration of Senior Secondary Schools in Niger State The objectives were to determine the influence of funding and infrastructural facilities on the school administration. Survey design was used. The population was 2875 with 382 sample size through a multistage sampling technique with twenty-five self-designed structured-items questionnaire. Reliability of the instrument was ascertained through pilot study via a test re-test method and the two results were correlated using Pearson Product Moment Correlation Coefficient (PPMC). The result was 0.94 which implies the instrument was reliable. Simple percentages and mean were the statistical tools for data analysis. The study revealed that adequate funding of facilitate effective school administration, government grants were not adequate to maintain and/or manage this school and poor school plant planning affect effective administration of school. It was recommended that principals should diversify revenue generation through farming and introduce skill acquisition programmes for students so as to sale the product in order to boost school funding, adequate and qualitative ICT facilities should be provided to facilitate effective school administration and principals should involve community through School-Based Management Committee (SBMC) to promote adequate provision of infrastructural facilities in senior secondary schools in Niger State, Nigeria.